REVIEW AND NEW DATA OF THE FOSSIL REMAINS FROM MONTE PEGLIA (LATE EARLY PLEISTOCENE, CENTRAL ITALY) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
After more than sixty years since its discovery, the fossils from Monte Peglia (late early Biharian, Umbria) are reconsidered in their entirety. The small mammals of Monte Peglia upper and lower levels had been studied in the past, whereas the remains of large mammals of Monte Peglia lower level, stored in several Institutions of central Italy, are described here for the first time. The following taxa have been described: Hystrix refossa, Homotherium latidens, Panthera cf. P. gombaszoegensis, Felis cf. F. lunensis, Canis mosbachensis, Vulpes alopecoides, Meles meles, Pannonictis cf. P. nestii, Mustela palerminea, Ursus cf. U. etruscus; Macaca sylvanus florentinus, Equus altidens, Stephanorhinus cf. S. hundsheimensis, Sus sp., Capreolus sp., Axis eurygonos, Hemitragus cf. H. orientalis, Bison degiulii. Moreover, the list of small mammals of the lower level has been updated with the addition of three new small vertebrate taxa: Rana sp., Myotis sp. (large size), cf. Miniopterus sp. The study of the remains of large mammals of the lower layer indicate the survival of a number of taxa of latest Villafranchian age. If we accept the biochronological correlation of Monte Peglia with the Colle Curti local fauna, its age should be ~1.072 Ma. In this case, it is possible to pinpoint the accumulation of the lower level to the MIS 35/33, as the small mammals confirm the presence of a mixed environment with forested and open spaces and warm temperate climate. The accumulation of the upper level, characterized by taxa typical of open spaces and steppes and a cooler climate, probably occurred during MIS 34/32.
Keywords: Biochronology; palaeoclimate; Biharian; Villafranchian; Galerian; vertebrates.